Copyright Protection in the NFT Ecosystem: Legal Challenges and Policy Recommendations for Indonesia - Mulfirana; Khausan, Makmur; Taufik, Moh (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Non-Fungible Tokens (NFTs) present significant opportunities for the creative industry in digitizing and monetizing artistic works. However, a major challenge arises in copyright protection, particularly in Indonesia, which has yet to establish specific regulations addressing NFTs within its intellectual property (IP) law framework. Currently, legal protection relies on Law No. 28 of 2014 on Copyright, which does not fully accommodate the characteristics of blockchain technology. This study aims to analyze copyright protection in Indonesia's NFT ecosystem, compare it with regulatory frameworks in the United States and the European Union, and provide policy recommendations that are more adaptive to the advancement of digital technology. The research adopts a normative juridical approach, incorporating comparative legal analysis and empirical studies through interviews with 15 key stakeholders, including digital artists and legal practitioners. The findings indicate that 78% of respondents perceive Indonesia’s current regulatory framework as ineffective in protecting NFT copyrights, whereas regulatory developments in the United States and the European Union have successfully reduced NFT copyright disputes by 40% over the past five years. Additionally, an analysis of 30 NFT-related disputes on OpenSea and Rarible reveals that 65% of cases involve copyright claims that cannot be effectively resolved through national legal mechanisms. This study recommends implementing a takedown notice mechanism, integrating smart contracts for creator royalties, and strengthening digital arbitration frameworks within Indonesia’s legal system. With clearer regulations, Indonesia’s NFT ecosystem is expected to develop with stronger legal protections for digital content creators